Building Alternative Schools for Indonesian Migrant Children in Malaysia: Uinsa International Community Engagement: Membangun Sekolah Alternatif Anak Migran Indonesia di Malaysia: Uinsa International Community Engagement - Moh Anshori; Moh Adam Rizki (Altifani Journal: International Journal of Community Engagement, 2025)
Building alternative schools for Indonesian migrant children is an important effort to fulfill the right to a proper education. Migrant children often face major challenges from limited access, social stigma, language barriers, and legal status. Alternative schools are a means of empowerment for migrant children by providing education that is responsive to conditions. Through a curriculum tailored to the cultural background and specific needs of migrant children, the school helps build confidence, independence, and better future opportunities. Through interactive learning methods and participatory approaches. Alternative schools aim to provide academic knowledge but also support the social and emotional adaptation process of migrant children. The involvement of the Indonesian migrant community and teacher training are important aspects in the implementation of alternative schools. Despite many challenges such as funding administration and social stigma, alternative schools are expected to be a sustainable solution in improving access to education for migrant children. With the initiative to build alternative schools to contribute to the social development and empowerment of migrant children, ensuring that they can develop their full potential in a supportive and Alternative schools are designed to provide adaptive education through empowerment programs, using a curriculum tailored to the cultural background and needs of migrant children.